The effect of social categorization on trust decisions in a trust game paradigm - Cañadas, Elena; Rodríguez-Bailón, Rosa; Lupiáñez, Juan (Frontiers in Psychology, 2015)
This study investigates whether participants use categorical or individual knowledge about others in order to make cooperative decisions in an adaptation of the trust game paradigm. Concretely, participants had to choose whether to cooperate or not with black and white unknown partners as a function of expected partners’ reciprocity rates. Reciprocity rates were manipulated by associating 3 out of 4 members of an ethnic group (blacks or whites consistent members) with high (or low) reciprocity rates, while the remaining member of the ethnic group is associated with the reciprocity of the other ethnic group (inconsistent member). Results show opposite performance’s patterns for white and black partners. Participants seemed to categorize white partners, by making the same cooperation decision with all the partners, that is, they cooperated equally with consistent and inconsistent white partners. However, this effect was not found for black partners, suggesting a tendency to individuate them. Results are discussed in light of the implications of these categorization-individuation processes for intergroup relations and cooperative economic behavior.